Designing motion marking menus for people with visual impairments. Issue 109 (January 2018) - Dim, Nem Khan; Kim, Kibum; Ren, Xiangshi
Highlights: We explored the potential of marking menus as a solution to current problems of people with visual impairments in using mobile devices. We proposed motion-based marking menus (MMM) for eyes-free interactions in smartphones for people with visual impairments. We investigated suitable number of menu items and levels of MMM that are usable for people with visual impairments. Users were able to perform marking menu selections in up to 8 directions. Based on the system criteria, we also suggested suitable menu levels. We assessed the efficiency of MMM relatively to current smartphone accessibility menu, TalkBack. Users could perform menu selections with MMM than with TalkBack. Users were also receptive to the new menu system, MMM. Abstract: Current smartphone accessibility for people with visual impairments relies largely on screen readers and voice commands. However, voice commands and screen readers are often not ideal because users with visual impairments rely mostly on hearing ambient sound from the environment for their safety in mobile situations. Recent research has shown that marking menus in mobile devices provide fast and eyes-free access for sighted users Francone et al., 2010; Oakley and Park, 2007, 2009. However, the literature is lacking design implications and adaptations that meet the needs of users with visual impairments. This paper investigates the capabilities of visually impaired people to invoke smartphone functions using marking menus via 3D motions. We explore and present the optimal numbers of menu items (breadth) and menu levels (depth) for marking menus that people with visual impairments can successfully adopt. We also compared a marking menu prototype to TalkBack™ which is an accessibility menu system in Android smartphones. The experimental results show that our participants could perform menu selections using marking menus faster than when using TalkBack. Based on the study results, we provide implications and guidelines for designing marking menus and motion gesture interfaces for people with visual impairments.